STRATEGIC INNOVATION AS DRIVER FOR SME PERFORMANCE IN YEMEN (Journal of Technology and Operations Management, 2018)
Success lies at the heart of every organization’s ability to innovate, innovation is one of the most important strategies of competition, both for large and small firms, it is widely held in the literature and among practitioners that small and medium enterprises (SME) are instrumental in the economic development of countries worldwide. However, the contribution of SMEs can only be possible through performance. This study is a conceptual discussion of manufacturing SME performance in Yemen and the effect of strategic innovation. The performance is considered to be very low, and the country is ranked by the Global Innovation Index as one the lowest in terms of innovation. The study discusses strategic innovation and presents a framework for understanding the concept in 10 different ways. It concludes by recommending some policies through which the government of Yemen can assist manufacturing SMEs. Specifically, the study recommends that the government should provide training subsidies to manufacturing SMEs because innovation can only take place when human resources are adequately trained.